Analisis Tata Kelola Data Digital pada Repositori UIN Antasari Banjarmasin - Anwary, Ahdie; Rozanti, Dwi Wahyu (Media Pustakawan, 2024)
This study aims to analyze digital data governance at the UIN Antasari Banjarmasin repository, digital data sustainability is one of the elements of knowledge management, this research uses the vosviewer application first to map the relationship between subjects related to digital data sustainability. the research method uses a qualitative approach with the research subjects, namely 3 managers of the digital repository of the UIN Antasari Banjarmasin library, research data collection in March-April 2023, data collection techniques: primary & secondary data. Primary data is collected through primary sources, namely interviews with repository managers and observations of repositories and eprints systems. Secondary data is collected with the results of previous research both from ebooks and books, journals, elements of digital data sustainability, namely all information must be open, information must also be complete and the information provided must be available whenever needed. The results of the research found related to the sustainability of digital data in the repository of UIN Antasari Banjarmasin are the need for awareness from the institution towards digital data management as a valuable asset, the importance of a shared understanding from the repository manager to the leadership towards the sustainability of digital data in higher education libraries, policies and sop related to digital information management need to be made and followed up so that the information storage space becomes effective and efficient, must be done.